2014
DOI: 10.1016/j.jchemneu.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal mossy fiber leu-enkephalin immunoreactivity in female rats is significantly altered following both acute and chronic stress

Abstract: Research indicates that responses to stress are sexually dimorphic, particularly in regard to learning and memory processes: while males display impaired cognitive performance and hippocampal CA3 pyramidal cell dendritic remodeling following chronic stress, females exhibit enhanced performance and no remodeling. Leu-enkephalin, an endogenous opioid peptide found in the hippocampal mossy fiber pathway, plays a critical role in mediating synaptic plasticity at the mossy fiber-CA3 pyramidal cell synapse. Estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 69 publications
11
58
0
Order By: Relevance
“…D, The MF synapse is illustrated schematically for a female on proestrous morning. The levels of enkephalins are higher in proestrous female rats compared with male rats (Pierce et al, 2014). D1, Basal transmission in proestrous females.…”
Section: Ptp and Ltpmentioning
confidence: 99%
See 4 more Smart Citations
“…D, The MF synapse is illustrated schematically for a female on proestrous morning. The levels of enkephalins are higher in proestrous female rats compared with male rats (Pierce et al, 2014). D1, Basal transmission in proestrous females.…”
Section: Ptp and Ltpmentioning
confidence: 99%
“…However, an effect of postsynaptic MORs on basal transmission would require enkephalin release, and it is generally assumed that neuropeptide release requires high-frequency stimulation (Cheng and Pomeranz, 1979;Bartfai et al, 1988;Thureson-Klein and Klein, 1990). Notably, extremely high frequencies of stimulation may not be required to release enkephalins in proestrous females because MF enkephalin levels increase at that time (Torres-Reveron et al, 2008;Pierce et al, 2014). In addition, dense core vesicles containing neuropeptides move closer to the plasma membrane in response to 17␤-estradiol (Tabatadze et al, 2013) Diestrous-1 females showed a smaller effect of naloxone and CTOP on basal transmission.…”
Section: Opioid Regulation Of Mf Fepspsmentioning
confidence: 99%
See 3 more Smart Citations